Development of an Oil Well Casing Program for Optimal Production - Tromo, Felicia Christelle Glawdys; Tankoua Nkojap, Gabriel Pascal; Malwe Boudoue, Hubert; Nyang Kibanya, Noel; Takougang Kingni, Sifeu (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This paper deals with the development of a casing program on a well called A4-1 (for confidentiality reasons) for safe and cost-effective production. The data used are geological data and information on different depths. To achieve the paper's objective, first, the different casing installation depths are determined using Excel software, and the mud program required for drilling, as well as the different casing diameters, are found through analysis of the tool selection diagram. After calculating the various pressures and loads, the drilling handbook is used to select the different grades for each casing. The results show that, at a depth of 6480 feet, the surface casing has a diameter of 11"3/4, weight of 65 ppf, and grade K55. At a depth of 9,200 ft, an 8"5/8 diameter casing is used, with a weight of 44 ppf, and a grade C90. At depths of 10333.6 ft, the production casing is 6''5/8 in diameter, weighs 32 ppf, and is grade C90. The investment for the casing is profitable for a casing installation time of one month.